Development of Test Chamber for Gas Insulation Testing and Measurement - Ahmed, Rizwan; Abd Rahman, Rahisham; Shahri, Muhd Hakimi Al Iqbal (Evolution in Electrical and Electronic Engineering, 2022)
This paper concerns about high-voltage components like circuit breakers, disconnect, and grounding switches in a metal pipe and insulates them with sulfur hexafluoride